Strength performance and chloride penetration of concrete using 100% coal bottom ash as coarse and fine aggregate replacement - Muhammad Nor Syahrul, Zaimi; Nur Farhayu, Ariffin; Sharifah Maszura, Syed Mohsin; N. H., Abdul Shukor Lim; Fadzil, Mat Yahaya; Khairunisa, Muthusamy; Saffuan, Wan Ahmad (IOP Science, 2021)
Since 1987, Malaysia had used coal as a product to generate electricity. One of the main or the largest power plant in Malaysia is Tanjung Bin power plant at kukup, Johor. As a coal-based power plant, tonnes of coal bottom ash had been burned every day and the waste without specific economic benefit winding up in the ash pool. Other than that, the expenses and environmental risk that concerns are involved with landfill ash reservoir, emphasis has now been centered on how to better manage this material waste. Therefore, this paper presents one of the alternative ways to manage the coal waste by cooperative it into concrete. This research study focuses on strength and durability performance of the concrete containing coal bottom ash as a coarse and fine aggregates replacement. The tests conducted was workability on fresh concrete, compressive strength test and chloride penetration test. The results show that the concrete containing coal bottom ash has low workability shear strength. For compressive strength test with the size of 100 mm × 100 mm × 100 mm cubes resulted compressive strength higher than control mix. For chloride penetration test, the specimens were immersed in 5% NaCl solution. The results show a better performance in term of strength compare to control specimen. Thus, it can be concluded that by using 100% replacement of bottom ash in concrete can produce comparable performance concrete with normal concrete as well as can reduce the waste generate to the landfill.